The usefulness and actual use of wearable devices among the elderly population. (January 2018) - Kekade, Shwetambara; Hseieh, Chung-Ho; Islam, Md. Mohaimenul; Atique, Suleman; Mohammed Khalfan, Abdulwahed; Li, Yu-Chuan; Abdul, Shabbir Syed
Highlights: A combined study of review on the usefulness of available wearable devices and survey on actual use of wearable devices. There are increasing number of wearable devices made available which can be used for elderly age groups. Age and sex equality and health status need to be considered during clinical assessment of the devices. The awareness and use of wearables among elderly is scant. Physical and mental activity wearable monitors are among the top future preferred devices. Abstract: Background and objective: Elderly populations are more prone to diseases and need continuous monitoring of parameters to ensure good health. Wearable devices (WDs) can be helpful in the early detection and management of medical conditions. However, less is known about the use of currently available WDs among elderly populations. The objectives of this study were to determine the usefulness and actual use of wearable devices among the elderly population. Methods: Our methodology was based on a systematic review and a survey questionnaire. In the systematic review, search was conducted in four databases PubMed, MDPI, Sage, and Scopus with search terms "wearable device" and "elderly", "wearable sensor" and "elderly". The inclusion criteria were the studies which described health-related wearable devices, its use as the outcome, conducted on a minimum of ten participants and published in the last five years. The survey was conducted on the MOOCs (Massive Open Online Course) platform. The questionnaire was related to the use of technology, intention to use, security and privacy concerns, and willingness to pay. Results: The review identified 4915 articles, of which, 31 studies eventually met the inclusion criteria. All studies reported positive impacts after assessing devices, despite certain drawbacks. The majority of the samples were males. The survey revealed responses from 233 individuals out of the 1100 participants of the course. The survey results were categorized into two age groups: 54.3% were elderly (>65 years) and 45.49% were non-elderly (≤65 years). Very few elderly people were currently using WD. More than 60% of elderly people were interested in the future use of wearable devices, and preferred future use to improve physical and mental activities. A majority of the respondents were female. Conclusions: This study suggests awareness should be created among elderly populations regarding the use of WDs for the early detection and prevention of complications and emergencies. Elderly populations are more prone to benefits from using WDs. The review concluded that devices should be tested on elderly groups as well, considering sex equality, and on both healthy and sick participants for better insights. The survey determined the elderly as frequent users of technology, but lack of knowledge of WD and demonstrated female interest in the use of WD. In future research on WDs, it is suggested that clinical studies be conducted for longer durations, and standard protocols such as age and sex equality should be considered. Requirements from both users and physicians should be acknowledged for better cognizance of WDs.